UNDERSTANDING ISLAMIC EDUCATION IN THE SULTANATE PERIOD PASAI - Diauddin (Journal of Educational Science Learning and Research, 2024)
Islam in Indonesia in the Middle Ages was influenced by royal figures, most of whom were kings because in the Middle Ages in Indonesia the kingdom period lasted from 13 AD – 18 AD. One of the kingdoms that adheres to Islamic teachings is the Samudrai Pasai kingdom, not only an Islamic kingdom but Samudra Pasai was the first Islamic kingdom in Sumatra. The aim of the research is to find out the figures who most influenced the spread of Islam in medieval Indonesia. Based on the analysis, it is known that Al-Shaleh is a figure who spread Islam in the Pacific Ocean of the archipelago to Southeast Asia. Changes that occurred during his leadership in the fields of law, economics and learning studies